Men and their families: Contributions of Caribbean men to family life: A discussion guide for use by groups in church, school, community and other settings - Brown, Janet (School of Continuing Studies, UWI, 1994)
The Caribbean Child Development Centre (CCDC) conducted a two-year research project to provide a socio-historical perspective on roles of Caribbean men within the family, and to survey and describe attitudes and behaviours of a cross-section of men in Jamaica. An eight-week series of discussions, designed for a maximum of 15 men and 15 women, was organized to cover the topics of the research. Among the findings of the survey and discussions were that men contribute more to family life than is credited, and that being a father has strong personal meanings for men. A result of the research project, this discussion guide for groups concerning parenting skills is designed to help men and women become better parents; to shape children from infancy into valued and responsible adults. Although it focuses on men's roles, the guide is written for use by both men and women. The eight workshop sessions outlined are: 1) "The Families We Come From;" 2) "The Families We Create;" 3) "Domestic Roles within the Family;" 4) "Peer Influences on Family Roles;" 5) "Relationships with Our Children;" 6) "Factors which Influence Personality Development;" and 8) "Putting it all Together." Guidelines for workshop facilitators are included
Keywords: Family relationship